Identification of the Synthesis of Guanosine Tetraphosphate (MS I) as Insertion of a Pyrophosphoryl Group into the 3′-Position in Guanosine 5′-Diphosphate - Sy, Jose (National Academy of Sciences, 1973)
The phosphate transfer system of Haseltine et al., consisting of a ribosomal wash obtained from a stringent strain of Escherichia coli, washed ribosomes, GTP, and ATP, was used to prepare large quantities of guanosine tetra- and pentaphosphates, the magic spot compounds MS I and MS II of Cashel and Gallant. In our hands, the Haseltine et al. system yielded predominantly guanosine tetraphosphate, ppGpp. This system was used exclusively in the described experiments, with ATP labeled with (32)P in the β- and γ-positions as donor. The β-label was found to produce a ppGp⃰p and the γ-label a ppGpp⃰. Furthermore, [(3)H]GDP + [γ-(32)P]ATP yielded ppGpp in a (3)H:(32)P ratio of 1:1. The results indicate a transfer of the terminal pyrophosphoryl group of ATP as a unit. The position of the transferred pyrophosphoryl was assayed for by preparation of pGp⃰ from ppGp⃰p with Zn(++)-activated inorganic pyrophosphatase from yeast. The pGp⃰ was then assayed with 3′-nucleotidase, which liberated practically all the labeled phosphate. This result indicate that the phosphate transfer from ATP to GDP yields guanosine 5′-diphosphate-3′-diphosphate.